Cobalt Sulfide as Counter Electrode in p‐Type Dye‐Sensitized Solar Cells. Issue 11 (22nd July 2016) - Congiu, Mirko; Bonomo, Matteo; Marco, Maria Letizia De; Dowling, Denis P.; Di Carlo, Aldo; Dini, Danilo; Graeff , Carlos F. O.
Abstract: We proposed a novel application of cobalt sulfide (CoS) in the configuration of transparent thin film as anode in p‐type dye‐sensitized solar cell (p‐DSC). The anodes here considered have been prepared using a water‐based method that is suitable for the large scale production of large‐area electrodes. The photoactive cathodes of the p‐DSC were mesoporous nickel oxide (NiO) thin films deposited via rapid discharge sintering. The NiO electrodes were sensitized with the benchmark dye erythrosine B (ERY), while the couple I − /I3 − was the redox mediator. The CoS anodes showed higher electrocatalytic efficiency in comparison with the commonly used platinized Fluorine‐doped Tin Oxide (Pt‐FTO). This was determined by means of electrochemical impedance spectroscopy of CoS based dummy cells, with CoS showing a lower charge‐transfer resistance with respect to Pt‐FTO. The overall conversion efficiency of the p‐DSC employing ERY‐sensitized NiO as photoactive cathode and CoS anode was 0.026 %, a value very close to that obtained with Pt‐FTO anodes (0.030 %). The external quantum efficiency spectra of the p‐DSCs with CoS anodes were similar to those obtained with Pt‐FTO anodes under illumination with AM 1.5 solar simulator. Abstract : The application of cobalt sulfide as counter electrodes in a p‐type dye sensitized solar cell, using I ‐ /I3 ‐ as redox electrolyte and erythrosine B as photosensitizer anchored to p‐type nickel oxide. The charge separation happens at the interface erythrosine//electrolyte after the absorption of a photon. In our configuration, the reduced redox mediator (I ‐ ) have been regenerated at the anode: a conducting transparent oxide (TCO) covered with a thin layer of CoS.